Stress and Coping Strategies Among Caregivers of Cancer Patients in a Tertiary Care Setting in Nepal - Poudel, Asmita; Regmi, Ranju; Dahal, Laxmi; Parajuli, Sagar; Bhatta, Kusumsheela; Pandey, Anjila; Chalise, Manisha (Health Prospect, 2024)
Background: Cancer represents a tremendous burden on patients, families, and society as it is the second leading cause of death worldwide. With patients going through disease-specific problems, their care providers also face a variety of challenges during and after their treatment. The main objective of this research was to assess the stress level and coping strategies adopted by caregivers of cancer patients attending B.P. Koirala Memorial Cancer Hospital in Nepal. Methodology: The study used a cross-sectional design at B.P. Koirala Memorial Cancer Hospital in Bharatpur, Nepal. Participants were selected through purposive sampling and data collection was done using a pretested interview questionnaire schedule. Standardized Kingston caregiver stress scale and Brief COPE inventory were used. A chi-square test was done to analyze the data. Results: More than half (56.5%) of the caregivers were found to have mild level of stress followed by 26.1% with moderate stress levels. Educational status, monthly income, relationship with patient were found to have significant association with stress level (p<0.05). Major coping strategies adopted by caregivers were praying and meditation (35.5%), accepting reality (34.8%), and seeking emotional support (22.5%). Conclusion: The study’s findings revealed a notable prevalence of stress among caregivers of cancer patients. It highlights the need for targeted efforts to address caregiver stress, tailoring strategies based on income and education levels. Special attention should be given to caregivers who are first-degree relatives, as they may require unique support mechanisms. Keywords: Cancer, Caregiver, Stress, Coping Strategies, Nepal